Effect of layered silicates on fibril formation and properties of PCL/PLA microfibrillar composites. Issue 8 (31st October 2015) - Kelnar, Ivan; Fortelný, Ivan; Kaprálková, Ludmila; Kratochvíl, Jaroslav; Angelov, Borislav; Nevoralová, Martina
ABSTRACT: The study deals with improvement of poly(ɛ‐caprolactone) (PCL) parameters by in situ forming of poly(lactic acid) (PLA) fibrils. This structure is achieved by preparation of the melt‐drawn microfibrillar composite (MFC) from the PCL/PLA 80/20 blend containing the organophilized montmorillonite (oMMT) added using various mixing protocols. Improved mechanical behavior corresponds to the micron‐sized fibrils formation and reinforcement of both polymer components by oMMT, and to increased crystalline phase content in the fibrillar PLA phase. Effective melt drawing is only possible after the rheological parameters of the polymer components have been modified by oMMT where the clay addition method and content are of primary importance. From the results obtained, it follows that the role of oMMT in MFC is quite complex, numerous clay‐induced effects may be contradictory and must be harmonized to achieve PCL‐based biodegradable MFCs with improved parameters. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43061. Abstract :